2003
DOI: 10.1016/s1535-6108(03)00134-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of HDM2 activity by the ribosomal protein L11

Abstract: The HDM2 protein plays an important role in regulating the stability and function of the p53 tumor suppressor protein. In this report, we show that the ribosomal protein L11 can interact with HDM2 and inhibit HDM2 function, thus leading to the stabilization and activation of p53. The inhibition of HDM2 activity by L11 shows some similarity to the previously described activity of ARF, and expression of either ARF or L11 can induce a p53 response. Enhancement of the interaction between endogenous L11 and HDM2 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
557
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(595 citation statements)
references
References 72 publications
35
557
1
2
Order By: Relevance
“…Western blot analysis of p53 expression showed that POLR1A interference did not stabilise the protein in rpL11-silenced cells (Figure 2f), thus demonstrating that rpL11 availability was necessary for p53 stabilisation in POLR1A-silenced cells. In order to rule out that p53 stabilisation in POLR1A-silenced cells might be due to the inactivation of MDM2 consequent to its nucleolar sequestration, as described in other experimental models (Bates et al, 1998;Lohrum et al, 2003;Bernardi et al, 2004), we also evaluated the distribution of MDM2 in control and POLR1A-silenced U2OS cells by immunocytochemistry. We found that POLR1A silencing did not induce any accumulation of MDM2 in nucleoli (Supplementary Figure S3).…”
Section: Polr1a Silencing Stabilises P53 Without Disrupting the Nuclementioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis of p53 expression showed that POLR1A interference did not stabilise the protein in rpL11-silenced cells (Figure 2f), thus demonstrating that rpL11 availability was necessary for p53 stabilisation in POLR1A-silenced cells. In order to rule out that p53 stabilisation in POLR1A-silenced cells might be due to the inactivation of MDM2 consequent to its nucleolar sequestration, as described in other experimental models (Bates et al, 1998;Lohrum et al, 2003;Bernardi et al, 2004), we also evaluated the distribution of MDM2 in control and POLR1A-silenced U2OS cells by immunocytochemistry. We found that POLR1A silencing did not induce any accumulation of MDM2 in nucleoli (Supplementary Figure S3).…”
Section: Polr1a Silencing Stabilises P53 Without Disrupting the Nuclementioning
confidence: 99%
“…In fact, the large subunit ribosome proteins rpL5, rpL11 and rpL23 were all reported to bind MDM2, thus inducing p53 stabilisation by inhibiting its E3 ubiquitin ligase function (Lohrum et al, 2003;Zhang et al, 2003;Bhat et al, 2004;Jin et al, 2004). The impairment of the nucleolar function has been proposed as a common denominator of many signalling pathways leading both to the suppression of MDM2 function and to p53 stabilisation and activation (Rubbi and Milner, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative, but not mutually exclusive, mechanism for p53 sensing the integrity of the translation process centers on the binding of Mdm2 to the ribosomal proteins L5, L11 and L23. [23][24][25][26][27] It is therefore tempting to speculate that upon translational stress that L5, L11 and/or L23 become accessible to negatively feedback upon Mdm2 and activate p53 (Figure 1). Likewise, p53 is covalently associated with 5.8S RNA, 28 which interacts with L5 and 5S RNA, both of which bind Mdm2.…”
Section: How Is the Checkpoint Sensed?mentioning
confidence: 99%
“…Nearly a decade later, in screens seeking out novel Mdm2 modulating proteins, the large subunit RPs RPL5, RPL11 and RPL23 were all reported to bind to Mdm2, block the E3 ubiquitin ligase function of Mdm2, and promote p53 accumulation (Lohrum et al, 2003;Zhang et al, 2003;Bhat et al, 2004;Jin et al, 2004). Following these initial reports, additional evidence subsequently was produced to support the roles of RPS7 (Chen et al, 2007;Zhu et al, 2009), RPL26 (Ofir-Rosenfeld et al, 2008 and RPS3 (Yadavilli et al, 2009) as Mdm2-binding partners.…”
Section: Introductionmentioning
confidence: 99%